Comparative analysis of branchial ionocytes in Caspian Sea zander, Sander lucioperca (Linnaeus, 1758) using Na+, K+-ATPase immunolocalisation at different salinities - Ahmadnezhad, Mohaddeseh; Oryan, Shahrbanoo; Bahmani, Mahmoud; Bourani, Mohammad Sayad (Indian Journal of Fisheries, 2016)
Gill morphology and branchial ionocyte variability were examined in zander Sander lucioperca (Linnaeus, 1758)fingerlings, having two different body weights (1 and 2 g) for a period of ten days following their transfer from freshwater to two different salinities (7 and 12‰ Caspian Sea water) using Na+, K+-ATPase (NKA) immunolocalisation. Survival rates and plasma osmolarity levels at the end of each salinity challenge were measured. By the end of the experiment, bothweight groups were able to survive and successfully acclimate to salinity change. The number and size of branchial ionocytes in the gills dramatically decreased in both size groups; while, the filament ionocytes in both weight groups reformed at the end of the acclimation period. The results indicated both groups to be in the same osmoregulatory developmental stage, despite difference in their body weight. Also, their blood osmotic pressure and gill ionocyte changes at different salinity were similar when transferred to iso-osmotic condition. Further studies are needed for complete understanding of zander osmoregulatory systems exposed to different salinities.